Pengaruh Penerapan Website E-Persuratan Terhadap Kinerja Kantor Kesyahbandaran Dan Otoritas Pelabuhan Kelas I Samarinda - Fira Amanda; Ismail; Fierda Nurany (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2024)
The aim of this research is to find out how the E-Persorat system is implemented and its influence on the Harbor Master's Office and Class I Samarinda Port Authority. This research uses a quantitative research design. The object of this research is the users of the E-Persuratan Website, namely all employees. The data analysis technique used was carried out with the help of statistics and the data analysis used was descriptive and multiple linear regression. The division of testing includes instrument requirements using validity and reliability tests, data analysis requirements testing using linearity tests and data analysis testing using multiple linear regression tests and hypotheses (T test). Based on the analysis test results, it was found that the implementation of the E-Persuratan website had an effect on the performance of the Harbor Master's office and the Samarinda Class I Port Authority. Meanwhile, the implementation of the governance system has no effect on office performance. The phenomenon of these results can be seen from the data validity test of the two variables which are considered valid, the reliability of the two variables is considered valid, the linearity of the two variables is calculated linearly, the multiple linear regression analysis shows that there is a unidirectional relationship between the two variables, while the hypothesis test shows that there is an influence on the variables Website Use and The system usage variable has no influence on office performance